2019
DOI: 10.1016/j.scr.2019.101599
|View full text |Cite
|
Sign up to set email alerts
|

Reporter gene-engineering of human induced pluripotent stem cells during differentiation renders in vivo traceable hepatocyte-like cells accessible

Abstract: HighlightsiPSC-derived hepatocyte-like cells (HLCs) rendered traceable in vivo.Reproducible lentivirus-based gene transfer during the differentiation process.Protocol and reporter expression did not negatively impact on HLC maturation.Proof-of-principle shown for whole-body SPECT/CT-afforded HLC in vivo tracking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The fluorescent co-reporter GFP in our fusion reporter NIS-GFP helped streamline generation of traceable cells for preclinical experimentation. 27 , 28 , 36 Notably, NIS-fluorescent protein fusion reporters have been shown previously (1) to be correctly localized to the plasma membrane and function in several different cell types (rodent and human cancer cells, 20 , 27 , 28 , 29 , 36 human CAR T cells, 49 and hepatocyte-like cells 29 ) and (2) to mediate uptake of various substrates similarly to unmodified NIS (for similar relative substrate uptake of NIS substrates, compare Figure S9 A, Diocou et al. 36 , and Khoshnevisan et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The fluorescent co-reporter GFP in our fusion reporter NIS-GFP helped streamline generation of traceable cells for preclinical experimentation. 27 , 28 , 36 Notably, NIS-fluorescent protein fusion reporters have been shown previously (1) to be correctly localized to the plasma membrane and function in several different cell types (rodent and human cancer cells, 20 , 27 , 28 , 29 , 36 human CAR T cells, 49 and hepatocyte-like cells 29 ) and (2) to mediate uptake of various substrates similarly to unmodified NIS (for similar relative substrate uptake of NIS substrates, compare Figure S9 A, Diocou et al. 36 , and Khoshnevisan et al.…”
Section: Discussionmentioning
confidence: 97%
“… 16 , 22 One of the most promising host reporter genes is the human sodium iodide symporter (NIS), which has been shown to be well tolerated in different cell types, including cancer cells, cardiomyocytes, stem cells, and T cells. 27 , 28 , 29 , 30 In a proof-of-principle study employing retroviral transduction methodology, we demonstrated ex vivo engineering of murine Tregs to express NIS and detected the cells in vivo 24 h after administration by SPECT imaging. 31 Importantly, it has also been shown recently that the radioactivity levels that can be expected to be taken up into T cells through NIS use during imaging did not cause lasting DNA damage in T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Section 3.1). Mammalian NIS has been used in a variety of cell tracking applications in animal models spanning a wide range of different cell types [45,[84][85][86][87][88][89][90][91][92]. This is a testament to both its excellent contrast in many applications, as NIS is only endogenously expressed in the thyroid and a few extra-thyroidal tissues (salivary glands, mammary glands, stomach and small intestine, testes; [22]), and its small anionic radiotracers being readily available for both PET and SPECT imaging (Tab.1).…”
Section: Host-compatible Reporters Versus Foreign Reportersmentioning
confidence: 99%
“…Whilst PSC-derived therapies are costly to produce, they have already entered early clinical trials [124], and as their use for treating a greater range of injuries and diseases comes ever closer to clinical reality, reporter gene studies become increasingly important. Most early PSC therapy tracking studies incorporated the reporter cassette via lentiviral transduction and utilised the firefly luciferase Radionuclide reporter gene imaging could help overcome this limitation, but it has been employed only by a few studies using human PSCs to date [92,123,125,126]. Additionally, while studies using lentiviral-mediated reporter expression have mostly demonstrated stable reporter expression following both differentiation and PSC expansion, the risk of epigenetic silencing and viral integration at unwanted genomic sites remains.…”
Section: Reporter Gene Afforded Pre-clinical Tracking Of Stem Cell Thmentioning
confidence: 99%
See 1 more Smart Citation